Bismuthene Arrays Harvesting Reversible Plating‐Alloying Electrochemistry Toward Robust Lithium Metal Batteries. Issue 2 (29th November 2022) - Ding, Yifan; Sun, Yingjie; Shi, Zixiong; Yang, Xianzhong; Yu, Xiaoyu; Wang, Xiaojing; Sun, Jingyu
Abstract : 3D lithiophilic skeletons have attracted enormous attention in homogenizing local current distribution and optimizing metal deposition in the pursuit of robust Li metal anodes. Nonetheless, their practicability is markedly plagued by the cumbersome production routes and mediocre Coulombic efficiency (CE) of Li plating/stripping. Herein, scalable in situ growth of uniform bismuthene arrays over commercial Cu foam via spontaneous galvanic replacement reaction is demonstrated. Exhaustive structural/electrochemical measurements in combination with theoretical calculations collectively disclose the reversible plating‐alloying mechanism, wherein the formed Li3 Bi alloy interphase aids to lower the Li nucleation overpotential and elevate the CE performance. The thus‐designed Li metal electrode sustains a stable cyclic operation at 1 mA cm −2 /1 mAh cm −2 for 1600 h. When paired with LiFePO4 and sulfur cathodes, the Li metal batteries enable gratifying rate capability and cycling durability. This straightforward maneuver opens a new frontier in the scalable manufacturing of pragmatic current collectors in an economic fashion. Abstract : Bismuthene arrays directly grown on Cu foam via spontaneous galvanic replacement reaction render reversible Li plating/stripping and dendrite‐free Li deposition. Structural/electrochemical characterizations in combination with theoretical calculations disclose a plating‐alloying mechanism, wherein formed Li3 Bi alloy interphase helps lower the Li nucleation overpotential and elevate the Coulombic efficiency. The thus‐assembled Li metal full batteries realize stable cyclic performances.